Medical Compliance and Income-Health Gradients - Case, Anne; le Roux, Ingrid; Menendez, Alicia (American Economic Review, 2004)
Wealthier people live longer and experience less morbidity than do poorer people, in both developed and developing countries. While the association between income and health status has been well documented, the mechanisms leading to this correlation are unclear. In this paper, we use data collected from an informal urban township in South Africa to examine the extent to which compliance with medical protocols plays a role in the observed income-health gradient. Specifically, we look at adherence to protocols among individuals diagnosed with hypertension.